Small Steps. - Sachar, Louis (New York : Random House, 2006)
Three years after being released from Camp Green Lake, Armpit is trying hard to keep his life on track.
5-8
Keywords: Juvenile delinquents - Rehabilitation - Fiction; Cerebral Palsy - Fiction; People with disabilities - Fiction; Siongers - Fiction; Interpersonal Relations - Fiction; African Americans - Fiction